The Role of Strategic Human Resource Management in Enhancing Organizational Innovation and Sustained Competitive Advantage - Ambreen Kamil; Muhammad Haseeb ur Rehman Rana; Sudhair Abbas Bangash; Areesha Siddiq, (Dialogue Social Science Review (DSSR), 2025)
This Study gives an introduction to SHRM, with particular focus on the purpose of coordinating human resource management for organizational objectives with the intention of realizing superior organizational performance. Explain how SHRM enhances organizational culture dynamism as a valuable component in relation to current business environment volatility. Very precisely it introduces what are intended as primary goals of this research, with an emphasis on investigating the connection between SHRM, organizational innovation, and sustainable competitive advantage and Analyze how these interconnections are important to know for organizations that are in a position to operate in competitive markets. Explain the type of research design which has been used in the conduct of the study, either quantitative with SEM using IBM AMOS Identify the sample size of 490 participants, and the procedure to be used for the selection of participants so as to have a sample that is representative of the population. Explain the used data collection technique like survey or interview etc. and also the instrument used to measure all the variables associated with SHRM and innovation. Conclude the key findings of the study by identifying the main academic and managerial implications indicating the existent connections between the alignment of the HR practices, the integrated adoption of innovative technologies in the field of HR, and the leadership development processes. Explain how these elements aid in establishing sustainability of competitive advantage for organization. On the basis of these insights, this paper discusses the implications for organizations and how SHRM can be used more effectively to foster innovation and to position an organization more competitively. Provide recommendations of how the findings of the study may be used in the development of recommendations regarding practical Human Resource Management issues.